2014
DOI: 10.1016/j.semnephrol.2013.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Autophagy by TGF-β: Emerging Role in Kidney Fibrosis

Abstract: Autophagy is a highly conserved homoeostatic mechanism for cell survival under conditions of stress, and is widely implicated as an important pathway in many biological processes and diseases. In progressive kidney diseases, fibrosis represents the common pathway to end-stage kidney failure. Transforming growth factor-β1 (TGF-β1) is a pleiotropic cytokine that has been established as a central mediator of kidney fibrosis. Recently emerging body of evidence from studies in renal cells in culture and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 68 publications
2
96
0
3
Order By: Relevance
“…Myofibroblast was the major source of extracellular matrix secretion. Renal tubular cells lost their epithelial phenotype and acquired new characteristic features of mesenchyme [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Myofibroblast was the major source of extracellular matrix secretion. Renal tubular cells lost their epithelial phenotype and acquired new characteristic features of mesenchyme [11] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that renal interstitial fibrosis is a concomitant pathological change in the occurrence and development of DN. 3 The disorder of matrix metalloproteinases and the tissue inhibitors of metalloproteinases (MMPS/TIMPs) have relation with nephropathy fibrosis. 4 Studies show that gap junction plays a significant role in ischemic renal injury and the occurrence and development of DN, and Cx43, Cx40 and Cx45 are the main connexins expressed in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Potent sources of this protein are either macrophages or injured tubular epithelium. Via downstream signalling pathways, TGF-β1 induces type I collagen and fibronectin production in interstitial fibroblasts [51]. The balance between synthesis and degradation of collagen is crucial for the maintenance of tissue homeostasis.…”
Section: Renal Interstitial Fibrosismentioning
confidence: 99%
“…In response to injury, they proliferate and produce excessive extracellular matrix. It has been shown that TGF-β1 induces autophagy in mesangial cells, thereby negatively regulating matrix production by the degradation of intracellular type I collagen [51]. Thus, TGF-β1 functions both as an inducer of collagen synthesis and as an inducer of autophagy and subsequent collagen degradation.…”
Section: Renal Interstitial Fibrosismentioning
confidence: 99%
See 1 more Smart Citation